2012
DOI: 10.3389/fimmu.2012.00003
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for B-Cell Lymphoma: Current Status and Prospective Advances

Abstract: Therapy for non-Hodgkin’s lymphoma has progressed significantly over the last decades. However, the majority of patients remain incurable, and novel therapies are needed. Because immunotherapy ideally offers target selectivity, an ever increasing number of immunotherapies, both passive and active, are undergoing development. The champion of passive immunotherapy to date is the anti-CD20 monoclonal antibody rituximab that revolutionized the standard of care for lymphoma. The great success of rituximab catalyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
86
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(86 citation statements)
references
References 135 publications
0
86
0
Order By: Relevance
“…Four major mechanisms have been proposed for the action of rituximab: antibody-dependent cellular cytotoxicity (ADCC) and phagocytosis, complement-dependent cytotoxicity (CDC), direct induction of apoptosis, and "vaccination effect" resulting from cross-priming. These mechanisms have been demonstrated in vitro and in mouse models, and clinical observations support their activity in patients [37].As a single agent or in combination with chemotherapy, rituximab was able to improve the overall response rate (ORR), the duration of response and OS in several lymphoma subgroups [37]. Findings from one large trial showed an improvement in OS in patients with previously untreated CLL given fludarabine, cyclophosphamide, and rituximab compared with those given chemotherapy alone [16].…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…Four major mechanisms have been proposed for the action of rituximab: antibody-dependent cellular cytotoxicity (ADCC) and phagocytosis, complement-dependent cytotoxicity (CDC), direct induction of apoptosis, and "vaccination effect" resulting from cross-priming. These mechanisms have been demonstrated in vitro and in mouse models, and clinical observations support their activity in patients [37].As a single agent or in combination with chemotherapy, rituximab was able to improve the overall response rate (ORR), the duration of response and OS in several lymphoma subgroups [37]. Findings from one large trial showed an improvement in OS in patients with previously untreated CLL given fludarabine, cyclophosphamide, and rituximab compared with those given chemotherapy alone [16].…”
mentioning
confidence: 95%
“…Among them, one of the most promising candidates is the fully human type I Ofatunumab. The monotherapy with this mAb seems to be ineffective in rituximab-refractory FL; however, studies of ofatumumab combined with CHOP chemotherapy in patients with FL are ongoing [37]. The mAb appears to be more effective in CLL than in FL, as demonstrated by the FDA approval and conditional approval in Europe for the treatment of refractory CLL [16].…”
mentioning
confidence: 99%
See 3 more Smart Citations